2021
DOI: 10.1039/d1ta02493k
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in wearable self-powered energy systems based on flexible energy storage devices integrated with flexible solar cells

Abstract: Wearable electronics are considered to be an important technology in the next-generation smart electronics. Meanwhile, the ever-increasing energy consumption and the growing environmental awareness have highlighted the requirements of green...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 135 publications
0
32
0
1
Order By: Relevance
“…It can be observed that the conductivity increases exponentially with the applied voltage at stage II, whereas ∇E Fn and ∇E Fp change relatively slowly, and results in the variation in leakage current being dictated by the variation in conductivity of the regions along path I (note that in fact the path in the x direction of leakage current I 2 is mainly composed of path I) at stage II. Consequently, the leakage current varies exponentially with the voltage at stage II and the value of the ideality factor m in Equation ( 2) should be 2 according to Equation (10). At stage III, the QFLS of the regions along path I is saturated, that is, E Fn -E Fp is a constant or varies particularly little.…”
Section: Theoretical Analysis Of Linear Exponential Variation or Satu...mentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that the conductivity increases exponentially with the applied voltage at stage II, whereas ∇E Fn and ∇E Fp change relatively slowly, and results in the variation in leakage current being dictated by the variation in conductivity of the regions along path I (note that in fact the path in the x direction of leakage current I 2 is mainly composed of path I) at stage II. Consequently, the leakage current varies exponentially with the voltage at stage II and the value of the ideality factor m in Equation ( 2) should be 2 according to Equation (10). At stage III, the QFLS of the regions along path I is saturated, that is, E Fn -E Fp is a constant or varies particularly little.…”
Section: Theoretical Analysis Of Linear Exponential Variation or Satu...mentioning
confidence: 99%
“…[9] With the continuous improvement of photoelectric conversion efficiency, solar energy accounts for an increasing share of the energy supply system, gradually becoming one of the main alternatives to fossil energy. [10] For most electronics, the operating voltage is generally 1.5$12.0 V (i.e., a few dry batteries or button batteries). For example, the silicon impact ionization metal-oxide-semiconductor (I-MOS) fieldeffect transistors require a supply voltage of $5.5 V. [11,12] Concerning the conventional single junction solar cells, the open-circuit voltage (V OC ) depends on the bandgap of the semiconductor material and the intensity of sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…Self-powered health monitoring systems are employed mainly to track the health vitals of players during exercise and training and for the regular health monitoring of elders. These systems are usually powered by batteries charged either by a conventional power source or by wearable energy harvesting devices, i.e., ferroelectric, thermoelectric, triboelectric, and piezoelectric [1]. Currently, our lives have been dramatically changed with the emergence of these wearable health monitoring systems.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, a gradual thinning of Si wafers for reduction of the panel cost takes place. This search for a thinner light absorbing layer is additionally motivated by the much wider flexible SC applicability [5][6][7] . Therefore, modern Si SC industry has been narrowed down to the motto "thinner & cheaper" resulted in 10-fold decrease in thickness (20 µ m) 8 representing ultrathin SC niche and extremely thin ( < 3 µ m) freestanding SC beating 12% efficiency 9 .…”
Section: Introductionmentioning
confidence: 99%